Multilayered Electroactive Polyaniline-ZnO Modified GCE for Electrochemical Detection of Paracetamol - Samuel Chufamo; Bezabih Kelita; Sintayehu Berhanu; Almaz Kemal; Alemu Lelago (Advances in Materials Science and Engineering)
Paracetamol (PC) is widely used for defensive and medicinal purposes for human beings. But their deposition in the human body will persuade thoughtful health risks. So, the enhancement of sensitive and selective techniques for the easy and fast detection of PC is extremely fundamental. Multilayered electroactive polyaniline-ZnO nanocomposite (NC) film was developed for PC detection which was based on the oxidation of PC with polyaniline doped zinc oxide on a glassy carbon electrode (PANI/ZnO/GCE). PANI and PANI/ZnO NCs were fabricated by both electrochemical and in-situ oxidative chemical polymerization methods. The morphology of PANI/ZnO shows that the polymer was distributed on the surface of ZnO, and the XRD pattern confirms that the average size calculated was 7.48 nm for PANI/ZnO. From UV-Vis measurements, the PANI/ZnO composite shows a redshift relative to PANI and ZnO. Moreover, FT-IR spectra show that chemical bonds and stretching are assigned to different peaks. Using differential pulse voltammetry, the fabricated PANI/ZnO/GCE electrochemical sensor displays good analytical performance for PC with detection limits of 4 × 10−8 M and a sensitivity of 2.571 mA/1 × 10−8 M with a linear concentration of PC within the range of 1.0 to 7.0 × 10−8 M.